Analisis Efek Pelat Berpori pada Serat Tanaman Ekor Kucing (Typha Latifolia) terhadap Koefisien Penyerap Suara - Masri; Suhaeri; Arhami; Machmud, Mohd. Nizar; Masri, M. Faris Aufa (Yayasan Kawanad, 2023)
This study aims to determine the value of the sound absorption coefficient of cat tail fiber (Typha latifolia) with the effect of weight and pore size resistance of the test sample plate. In this case the researchers made 6 test samples where each sample consisted of cat tail fibers weighing 50 grams and 75 grams with a diameter of 110 mm and a thickness of 20 mm, the test samples were arranged in layers with aluminimum plate resistance which had a pore size of 1 mm, 1.5mm, and 2.5 mm. Tests were conducted using the impedance tube transfer function method (ISO 10534-2:1998) at frequencies of 1/1 octave (125 Hz, 250 Hz, 500 Hz, 1000 Hz, 2000 Hz, 4000 Hz and 8000 Hz). The test results show that the sound absorption value at each frequency of each sample is relatively different. At a frequency of 125 Hz - 250 Hz the best sound absorption was obtained in the test sample with a pore size of 1 mm 75 g, at a frequency of 500 Hz the best sound absorption was obtained in the test sample with a pore size of 1.5 mm 75 g, at a frequency of 1000 Hz - 8000 Hz the best sound absorbing coefficient value occurred in the test sample with a pore size of 1 mm 75 g. From the graph it can be concluded that the pore size of the aluminum plate and density in each test sample can affect the sound absorption value.